Pengujian Konfigurasi Otomatis Penambahan Gateway Pada Virtual Router Menggunakan Aplikasi Otomatisasi Jaringan Berbasis Web - Elin Sylvania Ginting; Suroso Suroso; Irawan Hadi (STMIK Budi Darma, 2020)
Current router configuration is still done conventionally, which means that to configure routers in a complex network, a network administrator configures the routers one by one. This is very inefficient, because if the router you want to configure is done in hundreds or thousands of routers, then the time needed by a network administrator is very long. Therefore, automation is needed. This study creates a web-based network automation application with python, the paramiko library which functions as a bridge between the server and network devices using the SSH (Secure Shell) protocol, and the django framework that can configure IP Gateway automatically. Network automation is carried out in a simulation using the GNS3 application on a previously designed network topology. The network automation application testing method used is the black-box testing method. The output of this research is a website consisting of a user page and an admin page that can configure virtual routers automatically.